Intervención del terapista respiratorio en paciente masculino de 65 años con insuficiencia respiratoria aguda asociada a Covid-19. - Macías Acurio, Marcos Bryan (2022)
Acute respiratory failure (ARI) is the inability of the respiratory system to perform its basic function, which is the exchange of oxygen and carbon dioxide between the surrounding air and the circulating blood, which must be done effectively and adequately for the metabolic factor of the respiratory system organism needs taking into account the age of the patient. Coronavirus disease 2019 (COVID19) is a respiratory infection caused by a new coronavirus first detected in Wuhan in December 2019, this disease that is currently causing a global pandemic occupies a high mortality rate. The clinical case established in the intervention of the respiratory therapist in a 65-year-old male patient diagnosed with acute respiratory failure is justified due to the pandemic that we are experiencing as a result of Covid-19. A correct clinical assessment of the signs and symptoms that these patients present and furthermore the performance of complementary tests are of great help to accurately diagnose patients with suspicion of this pathology. The intervention of the respiratory therapist plays an important role in the management of patients with this disease since the administration of oxygen therapy is of utmost importance in the recovery of these patients. A correct management in these patients through a correct pharmacological treatment and the applied respiratory therapy techniques will help us to improve the clinical picture presented by patients with this disease at the time of being hospitalized.